IMMU-18. INTERPLAY BETWEEN IDH1 AND ATRX MUTATIONS GOVERN INNATE IMMUNE RESPONSES IN GLIOMAS. (9th November 2020) - Hariharan, Seethalakshmi; Bowie, Michelle; Hostettler, Janell; Roso, Kristen; He, Yiping; Roskoski, Martin A; Charbonneau, Casey; Keir, Stephen; Brown, Michael; Irvin, David; Zhang, Gao; Gromeier, Matthias; et al.
Abstract: Innate-based immunotherapies are becoming increasingly important for treating brain tumor patients. About 50% of WHO grade II and III gliomas carry mutations in IDH1 and ATRX genes. Mutant IDH1 results in the production of 2-hydroxyglutarate, an oncometabolite that promotes global metabolic and epigenetic alterations. ATRX is a SWI-SNF chromatin remodeling protein that is involved in cell cycle regulation and maintenance of genomic stability. Both IDH1 and ATRX mutations have been implicated in dysfunctional immune signaling in cancer cells. However, the interplay between these mutations in mediating innate immune responses has not been investigated in gliomas. We have derived human and mouse glioma cell lines carrying mutations in IDH1 ( IDH1 R132H ) and/or ATRX, which we then used to generate both immune competent and nude mice models. Treating the ATRX knockout (KO) cell lines with dsRNA-based innate stimuli led to an early induction in phospho-IRF3, and late induction in phospho-STAT1 and ISG15, suggesting that ATRX deletion may enable a potent activation of type I interferon production and sensitize glioma cells to dsRNA-based innate stimuli. Our syngeneic murine glioma models confirm a survival advantage for mice carrying ATRX-KO tumors. These tumors also exhibit enhanced infiltration of T-cells and expression of activated macrophage markers. On the other hand, presence of IDH1 R132H led to a suppression in baseline expression of key innate immune players, which could be rescued by the mutant IDH1 inhibitor, BAY-1436032. Cells harboring IDH1 R132H and ATRX-KO retained sensitivity to dsRNA indicating that IDH1 R132H does not dampen the ATRX KO-mediated sensitivity to dsRNA. Our models are under evaluation with a combination of BAY-1436032 and clinically relevant dsRNA-based innate therapies. Our data indicates the presence of an interplay between IDH1 and ATRX mutations that may regulate innate signaling in gliomas. Understanding the mechanisms governing this interplay may aid in designing therapies that exploit this interplay.